2021
DOI: 10.1186/s12943-021-01315-9
|View full text |Cite
|
Sign up to set email alerts
|

PARP inhibitor Olaparib overcomes Sorafenib resistance through reshaping the pluripotent transcriptome in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common human malignancies worldwide with very poor prognosis. Resistance to targeted therapeutic drugs such as sorafenib remains one of the major challenges in clinical treatment. In the present study, PARP1 was found to be highly expressed in human embryonic stem cells, but progressively decreased upon specified hepatic differentiation. Reactivation of PARP1 expression was also detected in HCC residual tumors after sorafenib treatment in xenograft mouse model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…As a key repair enzyme, PARP-1 ensures the stability of a tumor cell genome after treatment with DNA damaging chemotherapy agents [ 61 , 62 , 63 ]. PARP-1 is able to promote (directly or indirectly) epigenetic modifications, creating conditions for development of heterogeneity of tumor cells and formation of super-resistant clones in a heterogeneous population [ 64 ]. Another PARP-1-mediated mechanism of drug resistance is a non-lethal autophagy [ 65 , 66 , 67 ].…”
Section: Parp-1 and Oncological Diseasesmentioning
confidence: 99%
“…As a key repair enzyme, PARP-1 ensures the stability of a tumor cell genome after treatment with DNA damaging chemotherapy agents [ 61 , 62 , 63 ]. PARP-1 is able to promote (directly or indirectly) epigenetic modifications, creating conditions for development of heterogeneity of tumor cells and formation of super-resistant clones in a heterogeneous population [ 64 ]. Another PARP-1-mediated mechanism of drug resistance is a non-lethal autophagy [ 65 , 66 , 67 ].…”
Section: Parp-1 and Oncological Diseasesmentioning
confidence: 99%
“…A growing number of new approaches pair PARPis with agents targeted at specific molecular alterations in tumors. These molecularly targeted therapies include RTK inhibitors, checkpoint kinase 1/2 (CHK1/2) inhibitors, ATR inhibitors, Wee1 inhibition, PI3K inhibitors, HDAC inhibitors, IGFR inhibitors, Raf inhibitors, MEK inhibitors, or drugs interfering with sex hormone synthesis [ 242 , 243 , 244 , 245 ]. The special edge of PARPis was derived from the discovery of synthetic lethality.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, embryonic stem cell pluripotency was identified by IPA as a top canonical pathways of both genes mutated in cfDNA of HCC subjects and genes mutated in cfDNA in subjects with advanced fibrosis/cirrhosis, suggesting an essential role in both HCC development and HCC progression. It was previously suggested that DNA damage repair signaling is essential for the maintenance of stem cell pluripotency in HCC [ 65 ] and that p38 MAPK signaling, leading to F-actin reorganization and activation of nuclear factor erythroid 2-related factor 2-mediated oxidative stress response, collectively contribute to enhanced stemness of HCC cells [ 66 ]. EMT was identified as a top canonical pathway only in IPA analysis of HCC mutated genes, confirming its essential role in HCC progression in this study population as well.…”
Section: Discussionmentioning
confidence: 99%